THE ROLE OF MICROBIOME IN IMMUNE-MEDIATED UVEITIS - Pandilov, Stefan; Gjorgoski, Icko; Shekerinov, Natasha Trpevska; Nikolovska, Biljana; Boshkoska, Ana Trpeska; Vezenkoska, Marija; Guchev, Filip (Journal of Morphological Sciences, 2024)
The microbiome has important physiological functions and is an essential element in the control of the immune response in the body. Its dysbiosis is today associated with the pathogenesis of a number of diseases, including non-infectious uveitis. These are immunologically mediated conditions, where disruption of autotolerance towards intraocular structures and immune mimicry are the basis of the pathophysiological mechanism. The aim of this paper is to present the current knowledge related to this complex interaction between the microbiome and intraocular homeostasis, as well as directions for possible therapeutic solutions through quantitative and qualitative modification of the microbiota. During the preparation of this literature review, a meta-analysis of data obtained from several large databases was approached: PubMed, Medline and EMBASE. Keywords such as: non-infectious uveitis, microbiome, intestinal microbiome, probiotics, immune-mediated diseases, human microbiota were used in the search. The obtained results were selected, processed and didactically arranged in order to present relevant current scientific views. Keywords: non-infectious uveitis, microbiome, microbiota, dysbiosis, microbiome modulation.